1982
DOI: 10.1002/sce.3730660406
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward science: A quantitative synthesis

Abstract: Meta-AnalysisThe term "meta-analysis" refers to the quantitative synthesis of research findings. Glass (1976) describes it thus:Meta-analysis refers to the analysis of a large collection of analysis results from individual studies for the purpose of integrating the findings. (p. 3).The primary objective of any meta-analysis is to determine an overall effect size as a summary of related research. A secondary objective is to determine which factors contribute most to this effect size.While meta-analysis has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(65 citation statements)
references
References 32 publications
3
59
1
2
Order By: Relevance
“…Another finding from the previous research is the low up to moderate correlation between attitude and achievement (Freedman, 1997;Germann, 1988;Haladyna & Shauhnessy, 1982;Wilson, 1983). From a meta-analysis covering literature from 1970 to 1991, evidence was found that high-performing girls, "doing well" or "achieving" in science was closely linked with "liking" science (Weinburgh, 1995).…”
Section: Introductionmentioning
confidence: 95%
“…Another finding from the previous research is the low up to moderate correlation between attitude and achievement (Freedman, 1997;Germann, 1988;Haladyna & Shauhnessy, 1982;Wilson, 1983). From a meta-analysis covering literature from 1970 to 1991, evidence was found that high-performing girls, "doing well" or "achieving" in science was closely linked with "liking" science (Weinburgh, 1995).…”
Section: Introductionmentioning
confidence: 95%
“…Haladyna and Shaughnessy (1982) posited students' attitudes are determined by the teacher, the student and the learning environment. Simpson and Oliver (1990) later found the preparation of the teacher, the nature of the hands-on activities, and the student involvement in the learning are important variables in student attitude.…”
Section: Biotechnology Attitudes and Interestsmentioning
confidence: 99%
“…No one will contest the fact that instructors are an important source of variation and can dramatically influence student performance and attitudes in the classroom [30][31] so the first step was to make sure that each audience did not perceive the instructor differently. Departmental evaluations were used toward this purpose and analysis of these student evaluations showed there was no significantly different perception of the instructor in the two classes.…”
Section: Assessment Effortsmentioning
confidence: 99%